A macroeconomic disequilibrium model of the German credit market - Peter Winker (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1996)
Not all markets are always characterized by immediate market clearing, for example due to a delayed adjustment of quantities and prices. Macroeconometric disequilbrium models proved to be a valuable tool in assessing the relevance of such phenomena on goods and labour markets. Asymmetric information is the central ingredient of most theoretic models of credit markets allowing for a non market clearing price setting. However, often the empirical analysis is either restricted to the micro level or does not allow for disequilibrium at the macro level. In this paper a macromodel of the German credit market is constructed starting with a microeconomic theory of asymetric information. The resulting macroeconometric disequilibrium model is estimated for the market of loans to the private sector in West Germany 1975 - 1989. The results indicate that rationing on the credit market exhibited a relevant extent for several subperiods.
Keywords: 330; Finanzmarkt; Kreditrationierung; Ökonometrisches Makromodell; Asymmetrische Information; Deutschland